Evaluation of medical emergency team medication management practices in acute hospitals: A multicentre study. Issue 1 (January 2022) - Levkovich, Bianca J.; Jones, Daryl A.; Bingham, Gordon; Orosz, Judit; Dooley, Michael J.; Cooper, D. James; Kirkpatrick, Carl M.
Abstract: Background: Medical emergency teams use medications to rescue deteriorating patients. Medication management is the system of steps and processes, including prescribing, distribution, administration, and monitoring, to achieve the best outcomes from medication use. Systems or standards for medication management by medical emergency teams have not been defined. Objectives: The aim of the study was to propose potential solutions to improve medical emergency team medication management by evaluating medication supply and related medication management practices during medical emergency team activations and understanding clinicians' perceptions about medical emergency team medication management in acute hospitals. Methods: A prospective multicentre audit of intensive care unit–equipped hospitals in Victoria, Australia, was conducted. After advertisement and invitation via scheduled email newsletters to hospitals, a representative of the medical emergency team from each hospital self-administered an online audit tool during December 2019 and January 2020. Audit data were analysed descriptively, and perceptions were analysed using content analysis. Results: Responses were received from 32 of the 44 (72.7%) eligible hospitals. At 17 of the 32 (53.1%) hospitals, arrest trolleys provided medications for medical emergency team activations, in addition to arrest calls. At 15 of the 32 (46.9%) hospitals, separate, dedicated medical emergency team medication supplies were used to care for deteriorating patients. Dedicated medical emergency team supplies contained a median of 20 (range = 8–37) medications, predominantly cardiovascular (median = 8, mode = 7, range = 4–16) and neurological medications (median and mode = 6, range = 0–11). Variation was observed in all storage and other supply-related medication management practices studied. The four most frequent categories of clinicians' perceptions described systematic challenges with availability of the right medication in the right place at the right time. Conclusions: Current supply and related medication management practices and clinicians' perceptions demonstrated further development is necessary for medication management to meet the needs of medical emergency team clinicians and their patients.